Human Opportunity Index - Provinces : Equality of Children's Opportunities in Pakistan - Newman, John (World Bank, Washington, DC, 2014)
This paper complements the World Bank's recent report on poverty by providing some additional information on inequality. In contrast to reports that analyze measures of inequality of income or wealth (such as the Gini), this paper focuses on equality of opportunities of children, where opportunities refer to access to basic services and goods (access to education, health conditions and basic infrastructure) that improve the likelihood of children to maximize their human potential. It introduces a new metric to Pakistan, the Human Opportunities Index (HOI), that combines the overall coverage rate of the opportunity with a penalty for the share of access to opportunities that are distributed in an unequal fashion. The Human Opportunity Index was developed recently at the World Bank and has been estimated now for over 20 countries in Latin America and Africa.